MtVRN2 is a Polycomb VRN2‐like gene which represses the transition to flowering in the model legume Medicago truncatula. (April 2016) - Jaudal, Mauren; Zhang, Lulu; Che, Chong; Hurley, Daniel G.; Thomson, Geoffrey; Wen, Jiangqi; Mysore, Kirankumar S.; Putterill, Joanna
Summary: Optimising the timing of flowering contributes to successful sexual reproduction and yield in agricultural plants. FLOWERING LOCUS T ( FT ) genes, first identified in Arabidopsis thaliana (Arabidopsis), promote flowering universally, but the upstream flowering regulatory pathways can differ markedly among plants. Flowering in the model legume, Medicago truncatula (Medicago) is accelerated by winter cold (vernalisation) followed by long day (LD) photoperiods leading to elevated expression of the floral activator, FT‐like gene FTa1 . However, Medicago, like some other plants, lacks the activator CONSTANS ( CO ) and the repressor FLOWERING LOCUS C ( FLC ) genes which directly regulate FT and are key to LD and vernalisation responses in Arabidopsis. Conversely, Medicago has a VERNALISATION2‐LIKE VEFS‐box gene ( MtVRN2 ). In Arabidopsis AtVRN2 is a key member of a Polycomb complex involved in stable repression of Arabidopsis FLC after vernalisation. VRN2‐like genes have been identified in other eudicot plants, but their function has never been reported. We show that Mtvrn2 mutants bypass the need for vernalisation for early flowering in LD conditions in Medicago. Investigation of the underlying mechanism by transcriptome analysis reveals that Mtvrn2 mutants precociously express FTa1 and other suites of genes including floral homeotic genes. Double‐mutant analysis indicates that early flowering is dependent on functional FTa1 . The broad significance of our study is that we have demonstrated a function for a VRN2‐ like VEFS gene beyond the Brassicaceae. In particular, MtVRN2 represses the transition to flowering in Medicago by regulating the onset of expression of the potent floral activator, FTa1 . Significance Statement: VRN2‐ like Polycomb genes are widespread in eudicot families of the Rosid lineage, but their function in plants beyond the Brassicaceae, some of which like Medicago lack FLC as the major target of Arabidopsis VRN2, is unclear. Here, we show that MtVRN2 has an important role in repressing the transition to flowering in Medicago by repressing FTa1, a potent floral activator.